IMPFLEMENTASI MUDHARABAH (BASIDUOAN) TERNAK SAPI DI NAGARI LABUH JORONG AMPALU KETEK KECAMATAN LIMA KAUM KABUPATEN TANAH DATAR - Subuhi, Ilham Mul; Rahmadona, Rahmadona; Iska, Syukri; Arianti, Faridah (Universitas Islam Negeri Sumatera Utara, 2024)
This study focuses on the practice of cooperation in cattle husbandry between cattle owners as sohibul mal (capital owners) and cattle breeders in a particular area. In Jorong Ampalu Ketek Nagari Labuh, this study examines the basiduoan system of jawi (cattle) livestock from the perspective of fiqh muamalah (Islamic economic law) to understand how the mudharabah (cooperation) contract is implemented in practice. Data were obtained through field research with various methods such as direct interviews with basiduoan jawi actors, observation, and documentation. In its analysis, the study found that serious and skilled cattle breeders tend to get greater profits, while those who are less responsible can result in minimal profits. This shows that the results of this cooperation are highly dependent on the commitment and skills of the cattle breeders. The basiduoan jawi tradition is considered beneficial to both parties in economic cooperation based on the mudharabah system. However, the study also identified obstacles that hinder the implementation of this system in Jorong Ampalu Ketek. The research method used is field research with a qualitative descriptive approach. Data collection was conducted through observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and drawing conclusions, while data validity was strengthened through triangulation. Overall, this study provides a deep understanding of the practice of cooperation in cattle maintenance using an Islamic economic approach, and identifies the challenges faced in implementing this cooperation system at the location studied. Collaborative cattle maintenance, Basiduoan system, Mudharabah contract, Islamic economic approach, Implementation challenges